2011
DOI: 10.1098/rspa.2011.0220
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of a dielectric droplet through an interfacial electric pressure

Abstract: A corona discharge-assisted technique for spreading of a gently deposited dielectric droplet into a uniform thin film over a dry isothermal conductive substrate is proposed. The surface charge was built up over the droplet interface through ion bombardment using a sharp emitter electrode. Interaction of the surface charge density and intense electric field generates an interfacial electrical pressure and leads to a uniform axisymmetric spreading of the droplet in the radial direction. It was shown that the dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that the electrostatic forces can be used for spreading of dielectric layers [2,3]. A selective spreading of silicone oil due to the tangential component of electric forces over dielectric substrates was demonstrated in Ref.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that the electrostatic forces can be used for spreading of dielectric layers [2,3]. A selective spreading of silicone oil due to the tangential component of electric forces over dielectric substrates was demonstrated in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…[2]. Very recently, it was also shown that a dielectric droplet exposed to a perpendicular corona discharge expands uniformly over the grounded substrate [3]. The corona discharge accelerates the ionic clouds toward the substrate and develops a surface charge over the droplet interface.…”
mentioning
confidence: 98%
“…Reference [10] reported that there was a linear relation between the contact line velocity and the relationship between fall speed and fall height by using a high-speed video camera. Reference [11] demonstrated that the droplet expansion process can be controlled through variation of the ion injection current and /or discharge exposure time. Reference [12] and under a uniform electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Electrohydrodynamic instabilities formed on the surface of dielectric liquids are caused by extrusion of the latter from the discharge region. Two physical mechanisms of such an extrusion can be distinguished: the discharge ionic wind pressure [2] [3] and the electrostatic repulsion on the charged surface [4]- [14]. The ionic wind pressure is detected in dielectrics with a relatively high electrical conductivity, which ensures passage of a sufficiently high current of the barrier discharge through them.…”
Section: Introductionmentioning
confidence: 99%